Mentoring during Uncertain Times. Issue 5 (May 2021) - Termini, Christina M.; McReynolds, Melanie R.; Rutaganira, Florentine U.N.; Roby, ReAnna S.; Hinton, Antentor O.; Carter, Calvin S.; Huang, Sunny C.; Vue, Zer; Martinez, Denise; Shuler, Haysetta D.; Taylor, Brittany L.
Abstract : Scientific success is mainly supported by mentoring, which often occurs through face-to-face interactions. Changes to the research environment incurred by the Coronavirus 2019 (COVID-19) pandemic have necessitated mentorship adaptations. Here, we describe how mentors can broaden their mentorship to support trainee growth and provide reassurance about trainee development amid uncertain circumstances.